Covalent Bonding of Thermoplastics to Rubbers for Printable, Reel‐to‐Reel Processing in Soft Robotics and Microfluidics. Issue 7 (8th January 2018) - Taylor, Jay M.; Perez‐Toralla, Karla; Aispuro, Ruby; Morin, Stephen A.
Abstract: The lamination of mechanically stiff structures to elastic materials is prevalent in biological systems and popular in many emerging synthetic systems, such as soft robotics, microfluidics, stretchable electronics, and pop‐up assemblies. The disparate mechanical and chemical properties of these materials have made it challenging to develop universal synthetic procedures capable of reliably adhering to these classes of materials together. Herein, a simple and scalable procedure is described that is capable of covalently laminating a variety of commodity ("off‐the‐shelf") thermoplastic sheets to silicone rubber films. When combined with laser printing, the nonbonding sites can be "printed" onto the thermoplastic sheets, enabling the direct fabrication of microfluidic systems for actuation and liquid handling applications. The versatility of this approach in generating thin, multifunctional laminates is demonstrated through the fabrication of milliscale soft actuators and grippers with hinged articulation and microfluidic channels with built‐in optical filtering and pressure‐dependent geometries. This method of fabrication offers several advantages, including technical simplicity, process scalability, design versatility, and material diversity. The concepts and strategies presented herein are broadly applicable to the soft robotics, microfluidics, and advanced and additive manufacturing communities where hybrid rubber/plastic structures are prevalent. Abstract : A variety of commodity plastics are covalently bonded to silicone rubbers using a general and scalable process. When combined with laser printing, microfluidic soft robotic actuators as well as "lab‐on‐chip" systems with unique form factors and capabilities (e.g., microchannels with built‐in optical filtering, pressure‐dependent geometries, thin, multilayer architectures, and soft actuators with hinged articulation) are directly fabricated.